(untitled) (Research, Society and Development, 2021)
Objective: to investigate the evidence in the literature on the association between internet addiction and suicidal ideation in university students. Method: an integrative review of publications on the CINAHL, EMBASE, LILACS, MEDLINE, PubMed, PsycInfo, SciELO, SCOPUS, Web of Science and Biblioteca Virtual em Saúde databases was carried out, without restrictions regarding language or publication date. The final sample comprised 5 articles, which were organized and characterized according to author, year, method, sample, country, instruments and results. Results: the prevalence of internet addiction among university students ranged from 7.7% to 27.3%, and suicidal ideation from 7.4% to 36.1%. The results of simple logistic regression analyses showed a significant association between internet addiction and suicidal ideation, although on multiple logistic regression this association was not statistically significant for 2 out of the 5 studies reviewed. Subjects at risk of or with addiction to the internet had a significantly higher rate of suicidal ideation compared with controls. Conclusion: although the presence of association does not indicate causality, these findings serve as an early warning sign to parents, educators and health professionals, indicating the need for longitudinal studies to further elucidate this relationship.